Poetics of synthesis in James Joyce’s novels «Ulysses» and «Finnegans Wake» - Lameka, Natallia U. (Journal of the Belarusian State University. Philology, 2022)
The article deals with the poetics of synthesis in James Joyce’s novels «Ulysses» and «Finnegans Wake». The topicality of research is explained as follows: it is necessary to systematise various devices of synthetic nature in the writer’s oeuvre. The author’s usage of this poetics has been substantiated by his exhaustive comprehension of the world and humans and combination of the national and the universal in his texts. Joyce’s works have been analysed in the context of culture of the turn of the 19th and 20th centuries and the first half of the 20th century as an epoch of the most radical artistic experiments when writers kept on enhancing the language of literature with the help of devices stemming from other arts. There have been revealed conceptual and stylistic parallels between the novels «Ulysses» and «Finnegans Wake» and works of such authors as Virginia Woolf, Thomas Stearns Eliot, Alfred Döblin, Thomas Mann, Lewis Carroll, Boris Vian, Pablo Picasso, Salvador Dali, Max Ernst, Charlotte Salomon, and others. Accentuating the parallels between literary texts and painting, graphics, cinema, music and architecture allows to reveal the intermediality of J. Joyce’s prose. Special attention has been given to such constituents of the poetics of synthesis as synthesis of arts, synthesis of genres and literary forms, ekphrasis, musical discourse, cinematic devices, polyphony, hybrid imagery, constructed language, simultaneity, and polystylism.
Keywords: James Joyce; synthesis; synthesis of arts; synthesis of genres; polyphony; hybrid imagery; simultaneity; constructed language